Changes in Liver and Spleen Stiffness by Virtual Touch Quantification Technique after Balloon-Occluded Retrograde Transvenous Obliteration of Gastric Varices and Exacerbation of Esophageal Varices: A Preliminary Study - Takuma, Yoshitaka; Morimoto, Youichi; Takabatake, Hiroyuki; Tomokuni, Junko; Sahara, Akiko; Matsueda, Kazuhiro; Yamamoto, Hiroshi (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To assess liver stiffness (LS) and spleen stiffness (SS) values measured by virtual touch quantification (VTQ) technique in the monitoring of portal pressure and their usefulness for the prediction of the exacerbation of esophageal varices (EV) in patients with gastric varices undergoing balloon-occluded retrograde transvenous obliteration (B-RTO).Materials and Methods The LS, SS, and hepatic venous pressure gradient (HVPG) were measured in 20 patients both before and after B-RTO. The change in each parameter between the two groups (EV exacerbation and non-exacerbation groups) was compared by analysis of variance. The efficacy of the parameters for the prediction of the exacerbation of EV was analyzed using a receiver operating characteristic (ROC) curve analysis.Results 9 patients (40.9 %) exhibited an exacerbation of EV within 24 months after B-RTO. Signiﬁcant changes were observed in the HVPG and SS after B-RTO between the two groups (EV exacerbation group vs. non-exacerbation group: HVPG before 12.7 ± 4.4 mmHg vs. 11.0 ± 4.4 mmHg; HVPG after 19.6 ± 6.0 mmHg vs. 13.6 ± 3.1 mmHg P = 0.003; SS before 3.40 ± 0.50 m/s vs. 3.20 ± 0.51 m/s; SS after 3.74 ± 0.53 m/s vs. 3.34 ± 0.43 m/s P = 0.016). However, no signiﬁcant changes in LS were observed between the two groups. The area under the ROC curves of elevation in HVPG and SS for the prediction of the exacerbation of EV after B-RTO were 0.833 and 0.818, respectively.Conclusion Elevation of the HVPG and SS measured by VTQ after B-RTO was useful for the prediction of the exacerbation of EV.
Keywords: spleen stiffness; balloon-occluded retrograde transvenous obliteration; portal hypertension; virtual touch quantification